Análise das ações de educação ambiental do projeto Águas do São Francisco em Sergipe, 2014 - Machado, Cristyano Ayres (2018)
Globalization has demonstrated through the lack of interest in environmental preservation in developed countries, placing natural resources as secondary, regardless of the consequences of their management and use. Since Brazil has to greatly improve the water resources management process, especially in water quality in rural areas, which is much lower compared to urban centers, and this directly influences agriculture, health and sector, which has been undergoing great expansion in recent years, mainly aimed at exports. The Águas do São Francisco Project was aimed at bringing knowledge to residents of the lower São Francisco region of Sergipe, with environmental education, restoration of degraded areas, and interventions. Environmental education envisages the possibility of changing scenarios, bringing knowledge and changing lives with their contents, when correctly worked in society. The present work had the objective of verifying the evaluation of the environmental education actions of the Águas do São Francisco Project, the methodology used at the beginning of Mayer's work, which questioned the effectiveness and applications of these actions, later Calório's methodology was used for the construction of a sustainability index of environmental education actions. This methodology allows to evaluate an environmental education project, in a critical and practical way, to verify if there was an effective appropriation of knowledge by the target public involved in these actions. Mayer's methodology showed a qualitative analysis of his eight questions, which shows the efficiency and effectiveness of environmental education actions in the Lower São Francisco. Contemplating the proposal that leads us to reflect on a real appropriation of the knowledge of these developed actions. In the methodology proposed by Calório the quantitative indicators show that there was a fragility in some topics: field day, rice culture course, gender thematic workshop, environmental training. That notes the lack of effective public policies with the local reality, inadequate management of the Government, little adherence by the population involved in the project. Whose improvement would be for a greater dissemination and direction of actions to a more intense sensitization of the community that lives in the Irrigated Betume Perimeter.